Modelling and mapping weekly rainfall for crop planning in north-western Himalayan states - JANA, C; ALAM, N M; GHOSH, B N; RAJA, P; SHARMA, N K (The Indian Journal of Agricultural Sciences, 2021)
Modelling and mapping of weekly rainfall was carried out for NW Himalayan states of India for kharif crop planning. Based on the findings of the study it was observed that, J&K states with area coverage of 2.7 m ha witnessed maximum rainy days at 25 SMW indicating 1st week of July as optimum sowing time for kharif crops, whereas in HP, 26th SMW, i.e. 2nd week of July was maximum considering both rainfall amount and rainy days with 0.54 m ha area coverage. But, in case of Uttarakhand, it differs widely which ranges from 26-28 SMW for rainfall and 30-31 SMW for rainy days category in 0.68 m ha area. The spatial-temporal maps of rainfall distribution will help in site-specific decision making for entire kharif crop planning adjusted to different landforms.